Making good on donors’ desire to Do Development Differently - and Honig, Dan; Gulrajani, Nilima (Third World Quarterly, 2018)
AbstractForeign aid donors are increasingly focused on changing the way their development agencies function. This discourse has focused on desired qualities, including greater knowledge of local contextual realities, appropriate adaptation to context and greater flexibility to respond to changing circumstances. We argue that more attention needs to be devoted to the achievement of these qualities and turn to contingency theory to identify some under-exploited ways to ?do development differently?. The qualities sought by donors are emergent properties of complex organisational systems and will only be achieved through a micro-level and interlinked focus on the fundamentals of organisation.